The Routledge Companion to Literature and Economics - Seybold, Matt; Chihara, Michelle; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
The study of literature and economics is by no means a new one, but since the financial crash of 2008, the field has grown considerably with a broad range of both fiction and criticism. The Routledge Companion to Literature and Economics is the first authoritative guide tying together the seemingly disparate areas of literature and economics.Drawing together 38 critics, the Companion offers both an introduction and a springboard to this sometimes complex but highly relevant field. With sections on "Critical traditions," "Histories," "Principles," and "Contemporary culture," the book looks at examples from Medieval and Renaissance literature through to poetry of the Great Depression and novels depicting the 2008 financial crisis. Covering topics from Austen to austerity, Marxism to modernism, the collated essays offer indispensable analysis of the relationship between literary studies and the economy. Representing a wide spectrum of approaches, this book introduces the basics of economics, while engaging with essential theory and debate. As the reality of economic hardship and disparity is widely acknowledged and spreads across disciplines, this Companion offers students and scholars a chance to enter this crucially important interdisciplinary area.
1. Introduction --PART I: Critical traditions --2. What is literary knowledge of economy? 3. The politics of form and poetics of identity in postwar American poetry 4. Rhetorical economics 5. Labor without value, language at a price: toward a narrative poetics for the financial turn --PARTII: Histories --6. Premodern economics: ideas, literature, and contexts 7. John Smithand the virus of trade 8. Gothic economies: capitalism and vampirism 9. The print revolutionand paper money 10. The economics of American literary realism 11. Womens writingand the mainstreaming of political economy 12. Modernismand macroeconomics 13. American modernismand the crash of 1929 14. Friedrich Hayekand the pleasures of liberal thoughtof modern Japan 15. Free trade masculinity and the literature of NAFTA --PARTIII: Principles --16. Asymmetric information 17. Black markets 18. Classical economics 19. Consumption: cultures of crisis. overprotection, and twenty-first-century literature 20. Corporate space 21. Currency 22.Literature and energy 23. Financialisation 24. Globalisation: everything in chains; the aesthetics of global capitalism 25. Inflation 26. Keynesand Keynesianism 27. Neoclassical economics 28. Neoliberalism 29. Real-estate confessions: moral realism in a risk economy 30. Reproduction 31. Secular stagnation and the discourse of reproductive limit 32. Social want 33. Speculation --PARTIV: Contemporary culture --34. "The real home of capitalism": The AOL Time Warner merger and capital flight 35. --Hamilton, credit,andAmerican enterprise 36. Global financeand scale: literary form and economics in Mohsin Hamid's --How to Get Filthy Rich in Rising Asia 37. Behavioral economics and genre 38. Serialization in the age of finance capitalism
Includes bibliographical references and index.
Also available in print format.
Keywords: Economics and literature; Economics in literature; Electronic books